Association of maternal low‐carbohydrate‐diet score during pregnancy with allergic diseases at 2 years of age. Issue 9 (6th September 2022) - Chen, Xi; Lin, Lixia; Huang, Li; Wu, Meng; Tan, Tianqi; Li, Qian; Zhong, Chunrong; Wang, Huanzhuo; Wang, Weiming; Sun, Guoqiang; Yi, Nianhua; Yang, Xuefeng; et al.
Abstract: Background: We prospectively evaluated the association between low‐carbohydrate‐diet (LCD) score during pregnancy and the risk of allergic diseases in infants up to 2 years. Methods: Participants were from a prospective mother‐offspring cohort study in Wuhan, China. LCD score was calculated according to the percentage of dietary energy intake from carbohydrate, protein, and fat assessed in late pregnancy using validated food frequency questionnaires. Allergic diseases, including immunoglobulin E (IgE)‐mediated allergic diseases, allergic contact dermatitis, and food allergy, were recorded at 3, 6, 12, and 24 months postpartum follow‐up. Poisson regression models were used to calculate relative risks (RRs) and 95% confidence intervals (CIs). Results: Among 1636 mother–infant pairs included in the present analysis, 230 infants (14.1%) with IgE‐mediated allergic diseases, 77 (4.7%) with allergic contact dermatitis, and 488 (29.8%) with food allergy were, respectively, reported. Independent of total energy intake and other potential confounders, both the lowest quintile (RR, 1.77; 95% CI, 1.13–2.77) and the highest quintile (RR, 1.72; 95% CI, 1.22–2.63), were associated with the risk of IgE‐mediated allergic diseases compared with the middle quintile. Among high‐carbohydrate‐diet pregnant women, substituting 5% of energy from either protein or fat for carbohydrate was associated with a lower risk of IgE‐mediated allergic diseases. While among low‐carbohydrate‐diet pregnant women, substituting 5% of energy from carbohydrate, especially high‐quality carbohydrate, for fat was associated with a lower risk of IgE‐mediated allergic diseases. Conclusion: Maternal low carbohydrate‐high protein and fat, and high carbohydrate‐low protein and fat diet were both associated with an increased risk of allergic diseases in the infants up to 2 years. This study may provide an intervention strategy for allergy prevention in early childhood.